Análisis de los desequilibrios del sector externo. Aplicación al caso argentino - Lanteri, Luis (2007)
The financial and exchange rate crisis observed in Argentine at the end of 2001 showed the importance of understanding the factors that explain the evolution of the balance of payments and, in particular, of the current account. The objective of this work is to show recent developments in the theory of the current account and its application to the Argentine case. In the first place, short and long term correlations between national saving and domestic investment is considered through a model of a mechanism of correction of errors. Later, the paper analyzes the main shocks that affect to the current account in agreement with different theories. Finally, the paper shows the intertemporary approach of the current account. In this case, the paper considers a standard version of this approach and a model that makes flexible some of its main basic assumptions.